Injustice for all: Mapp vs. Ohio and the Fourth Amendment - Zotti, Priscilla H. (Teaching texts in law and politics, 2005)
With its original documents and extensive interviews, Injustice for All is an authentic voice for civil liberties and change and the consequences that result. The book details the historical, legal, and political significance of the famous search-and-seizure case Mapp v. Ohio. From the underworld of gambling in 1960s Cleveland to the chambers of the Warren Court justices, the obscenity case becomes the vehicle for implementing the exclusionary rule. Dollree Mapp, the police who searched her, and all the major participants are followed throughout the investigation. The private papers of the justices reveal the inner workings of the nation's highest court. This book is essential for anyone interested in civil liberties and the processes of government as well as students of criminal justice and constitutional law